2009
DOI: 10.1002/jso.21360
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgical staging in locally advanced cervical cancer and subsequent chemotherapy

Abstract: SS in cervical cancer is a feasible and safe pretreatment procedure, and when associated with CT, it improves OS and DFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…Our results suggested that the response of lymph nodes to RT was a more significant predictive factor for PLN control than size of lymph node before RT or dose of external radiation. In several reports on lymphadenectomy for advanced cervical cancer, 39-45 % patients had PLN metastases [13][14][15]. In the current study, only 31.8% patients had PLN metastases based on our criteria.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Our results suggested that the response of lymph nodes to RT was a more significant predictive factor for PLN control than size of lymph node before RT or dose of external radiation. In several reports on lymphadenectomy for advanced cervical cancer, 39-45 % patients had PLN metastases [13][14][15]. In the current study, only 31.8% patients had PLN metastases based on our criteria.…”
Section: Discussioncontrasting
confidence: 49%
“…Several researchers have reported that 39-44% of patients with advanced cervical cancer have pelvic lymph node (PLN) metastases (based on lymphadenectomy) [13][14][15]. However, as many lymph node metastases cannot be detected by computed tomography (CT) or magnetic resonance imaging (MRI), RT for locally advanced cervical cancer includes prophylactic irradiation to the PLN area as standard radiation therapy for advanced cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the predominant failure for node-positive patients was distant metastases, especially in PANs. Marana et al [16] reported that surgical debulking achieved significantly improved OS (surgical debulking, 80.6%; non-surgical treatment, 51.1%; P = 0.001). In contrast, Cheung et al [7] and Kupet et al [17] indicated that surgical debulking did not have a positive effect on the OS.…”
Section: Discussionmentioning
confidence: 99%
“…Hacker et al [5] reported that severe late complications occurred in six patients (18%); five of these complications were small bowel obstructions, and one patient developed ischemic bowel in the distribution of the superior mesenteric artery necessitating resection of the small bowel and a duodenocolic anastomosis. Marana et al [16] also indicated that 9 of 36 patients (25%) had late complications.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have reported that 39–44% of patients with advanced cervical cancer have pelvic lymph node (PLN) metastases (based on lymphadenectomy) [1315]. However, as many lymph node metastases cannot be detected by computed tomography (CT) or magnetic resonance imaging (MRI), RT for locally advanced cervical cancer includes prophylactic irradiation to the PLN area as standard radiation therapy for advanced cervical cancer.…”
Section: Introductionmentioning
confidence: 99%